2015
DOI: 10.4103/0976-500x.149141
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse drug reactions of imatinib in patients with chronic myeloid leukemia: A single-center surveillance study

Abstract: Objective:To monitor the adverse drug reactions (ADRs) associated with imatinib treatment in patients with chronic myeloid leukemia (CML) in a tertiary care hospital.Materials and Methods:The study was carried out by the Departments of Pharmacology and Medical Oncology, Jawaharlal Institute of Postgraduate Medical Education and Research (JIPMER), Puducherry, India. The study was carried out from March 2012 to February 2014. The ADRs were reported in a suspected Adverse Drug Reaction Reporting form, provided by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Imatinib is a tyrosine kinase inhibitor clinically applied against leukemia and metastatic gastrointestinal stromal tumors (Cismowski, 2007a). Nausea, vomiting, abdominal pain, and elevated serum transaminase level are associated with imatinib therapy (Cismowski, 2007a; Francis et al., 2015; Cross et al., 2006; Tonyali et al., 2010). On the other hand, nephrotoxicity and acute renal failure might accompany imatinib administration (Cismowski, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Imatinib is a tyrosine kinase inhibitor clinically applied against leukemia and metastatic gastrointestinal stromal tumors (Cismowski, 2007a). Nausea, vomiting, abdominal pain, and elevated serum transaminase level are associated with imatinib therapy (Cismowski, 2007a; Francis et al., 2015; Cross et al., 2006; Tonyali et al., 2010). On the other hand, nephrotoxicity and acute renal failure might accompany imatinib administration (Cismowski, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Imatinib is associated with mild to moderate toxicity, mostly reversible by dose reduction or discontinuation of the drug. In a study by Francis J et al ,[ 18 ] it was observed that thrombocytopenia was the most common adverse effect with a percentage occurrence of 57.9%, which is midway between the frequency reports in earlier Indian studies (17.5%–98.0%). Whereas, it was observed that maximum number of patients (46%) was having no side effects of Imatinib therapy; 23% patients suffered from edema, 12% from rashes, 9% with asthenia, 6% hyper pigmentation, 3% hypo pigmentation and 1% with pleural effusion.…”
Section: Discussionmentioning
confidence: 69%
“…Imatinib can cause side effects including weight gain, fatigue (Jabbour & Kantarjian, 2020), bone and muscle pain, as well as increased creatinine. A study conducted by Francis et al reported that 68% of CML patients treated with Imatinib experienced various side effects, especially hematological toxicity-thrombocytopenia as much as 21% (Francis et al, 2015).…”
Section: Resultsmentioning
confidence: 99%